2015
DOI: 10.1002/andp.201500008
|View full text |Cite
|
Sign up to set email alerts
|

Matter‐antimatter asymmetry ‐ aspects at low energy

Abstract: The apparent dominance of matter over antimatter in our universe is an obvious and puzzling fact which cannot be adequately explained in present physical frameworks that assume matter-antimatter symmetry at the big bang. However, our present knowledge of starting conditions and of known sources of CP violation are both insufficient to explain the observed asymmetry. Therefore ongoing research on matter-antimatter differences is strongly motivated as well as attempts to identify viable new mechanisms that could… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Significant deviations from previous measurements are found which are, if ascribed entirely to the angular acceptances of various experimental systems, in quantitative accord with ab initio theoretical predictions of the differential elastic scattering cross section. DOI: 10.1103/PhysRevLett.117.253401 While the apparent imbalance between matter and antimatter in the Universe remains a major puzzle in science [1,2], much progress in the understanding of the interactions between the two has been achieved through studies of controlled collisions of positrons ðe þ Þ and positronium (Ps, the short-lived atom made of an electron and a positron) with atoms and molecules [3][4][5][6][7].At low energies, the static and polarization interactions tend to cancel for positrons reducing their scattering probability in comparison with electrons. However, polarization often enhances direct ionization by positrons, so that they can be more penetrating and more ionizing than electrons, a result of potential import in analyses of astrophysical (e.g., [8]) and atmospheric events (e.g., [9]) as well as in positron-track simulations for dosimetry in positron emission tomography (e.g., [10]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant deviations from previous measurements are found which are, if ascribed entirely to the angular acceptances of various experimental systems, in quantitative accord with ab initio theoretical predictions of the differential elastic scattering cross section. DOI: 10.1103/PhysRevLett.117.253401 While the apparent imbalance between matter and antimatter in the Universe remains a major puzzle in science [1,2], much progress in the understanding of the interactions between the two has been achieved through studies of controlled collisions of positrons ðe þ Þ and positronium (Ps, the short-lived atom made of an electron and a positron) with atoms and molecules [3][4][5][6][7].At low energies, the static and polarization interactions tend to cancel for positrons reducing their scattering probability in comparison with electrons. However, polarization often enhances direct ionization by positrons, so that they can be more penetrating and more ionizing than electrons, a result of potential import in analyses of astrophysical (e.g., [8]) and atmospheric events (e.g., [9]) as well as in positron-track simulations for dosimetry in positron emission tomography (e.g., [10]).…”
mentioning
confidence: 99%
“…Significant deviations from previous measurements are found which are, if ascribed entirely to the angular acceptances of various experimental systems, in quantitative accord with ab initio theoretical predictions of the differential elastic scattering cross section. DOI: 10.1103/PhysRevLett.117.253401 While the apparent imbalance between matter and antimatter in the Universe remains a major puzzle in science [1,2], much progress in the understanding of the interactions between the two has been achieved through studies of controlled collisions of positrons ðe þ Þ and positronium (Ps, the short-lived atom made of an electron and a positron) with atoms and molecules [3][4][5][6][7].…”
mentioning
confidence: 99%
“…The observation of permanent electric dipole moments (EDMs) in elementary particles, atoms, and molecules could provide hints towards physics beyond the Standard Model of particle physics [1,2]. A considerable number of experiments to search for EDMs are currently underway in several independent experiments, which employ different sample materials.…”
Section: Introductionmentioning
confidence: 99%
“…The violation of the combined charge conjugation and parity operation, CP, is of particular importance because of the possible relation to the observed matter-antimatter asymmetry in the universe [1,2]. A. Sakharov [3] has suggested that the asymmetry in matter-antimatter may be explained via CP-violation in the early universe in a state of thermal non-equilibrium together with baryon number violating processes [4]. CP violation has been observed in neutral K and B meson systems, however, the known sources of CP-violation in the SM are insufficient to account for it [1].…”
Section: Introductionmentioning
confidence: 99%